Report of Another Mutation Proven Case of Carbonic Anhydrase II Deficiency - Satapathy, Amit Kumar; Pandey, Swati; Chaudhary, Madhumita Roy; Bagga, Arvind; Kabra, Madhulika; Uwe, Kornak; Gupta, Neerja (Journal of Pediatric Genetics, 2019)
Carbonic anhydrase (CA) II deficiency results in an uncommon type of autosomal recessive sclerosing bone dysplasia with renal tubular acidosis and intracerebral calcification. We report a classic case of CA II-associated osteopetrosis with a previously reported homozygous frameshift mutation. Child was evaluated for short stature and failure to thrive. He was diagnosed as osteopetrosis in view of the presence of hepatosplenomegaly and increased bone density though hematological parameters were normal. Further evaluation showed presence of associated distal renal tubular acidosis raising a possibility of CA II deficiency. Mutation analysis revealed a previously reported homozygous frameshift mutation c.143-146delCTGT (p.Ser48Phefs*9) in CA2.Child has normal growth after initiation of alkali therapy.
Keywords: osteopetrosis; renal tubular acidosis; CA II deficiency